Stoichiometry of microbial carbon use efficiency in soils. Issue 2 (May 2016) - Sinsabaugh, Robert L.; Turner, Benjamin L.; Talbot, Jennifer M.; Waring, Bonnie G.; Powers, Jennifer S.; Kuske, Cheryl R.; Moorhead, Daryl L.; Follstad Shah, Jennifer J.
Abstract: The carbon use efficiency (CUE) of microbial communities partitions the flow of C from primary producers to the atmosphere, decomposer food webs, and soil C stores. CUE, usually defined as the ratio of growth to assimilation, is a critical parameter in ecosystem models, but is seldom measured directly in soils because of the methodological difficulty of measuring in situ rates of microbial growth and respiration. Alternatively, CUE can be estimated indirectly from the elemental stoichiometry of organic matter and microbial biomass, and the ratios of C to nutrient‐acquiring ecoenzymatic activities. We used this approach to estimate and compare microbial CUE in >2000 soils from a broad range of ecosystems. Mean CUE based on C:N stoichiometry was 0.269 ± 0.110 (mean ± SD). A parallel calculation based on C:P stoichiometry yielded a mean CUE estimate of 0.252 ± 0.125. The mean values and frequency distributions were similar to those from aquatic ecosystems, also calculated from stoichiometric models, and to those calculated from direct measurements of bacterial and fungal growth and respiration. CUE was directly related to microbial biomass C with a scaling exponent of 0.304 (95% CI 0.237–0.371) and inversely related to microbial biomass P with a scaling exponent of −0.234 (95% CI −0.289 to −0.179). Relative to CUE, biomass specific turnover time increased with a scaling exponent of 0.509 (95% CI 0.467–0.551). CUE increased weakly with mean annual temperature. CUE declined with increasing soil pH reaching a minimum at pH 7.0, then increased again as soil pH approached 9.0, a pattern consistent with pH trends in the ratio of fungal : bacteria abundance and growth. Structural equation models that related geographic variables to CUE component variables showed the strongest connections for paths linking latitude and pH to β‐glucosidase activity and soil C:N:P ratios. The integration of stoichiometric and metabolic models provides a quantitative description of the functional organization of soil microbial communities that can improve the representation of CUE in microbial process and ecosystem simulation models.